Investigation of visual performance and visual complaints during reading using video oculography (VOG) / Noor Suhailly Saiman - Saiman, Noor Suhailly (2017)
The visual performance and visual complaints during reading were investigated. The visual performance was measured in term of eye movement and reading speed in a range of refractive power and was examined by using Video Oculography. The association between visual complaints (asthenopia and blurriness) and induced prism adaptation was studied too. Fifty young adults aged between 19 and 34 years old (mean: 22.63, SD: 1.97 years) with refractive errors between +0.50D and -6.00D (mean: -1.77D SD: 1.97D) were recruited in this study. Subjects were required to read the 200 words text at 40 cm while the eye movement and the reading speed were recorded using video oculography (VOG). Subjects were then required to wear induced base-in (IPD and 3PD) and base-out (IPD and 3PD) prisms. They were required to adapt for 30 minutes with each pair of induced prism. After the adaptation, they were required to read the short text. The occurrence of the visual complaints (asthenopia and blurriness) during reading was recorded. Spearman correlation coefficient revealed insignificant correlation between refractive error and reading speed (rs=0.18, p>0.05), saccades (rs=-0.20, p>0.05), fixations (rs=-0.30, p>0.05) respectively. A moderate negative correlation was found between regressions and refractive error (rs=-0.50